Analisis Gaya Kepemimpinan Otoriter pada PT Xyz - Diaz Ramdan Zulkurnain; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
Leadership traits emerge in a person when one group member can change and arouse the motivation of other members in the group so that the group can be directed, structured and coordinated in achieving goals effectively and efficiently. Leadership is related to how to influence other people, followers and subordinates in a company to achieve the goals desired by a leader. In line with the discussion of the methodology, this research uses a qualitative descriptive method, namely research that attempts to describe a symptom, event, event that is occurring in the present. In this research, the researcher tries to photograph events and occurrences that are of central concern, and then describe them as they really are. As for descriptive descriptive research on solving a problem that exists in the present, this research will describe the phenomena that occur regarding Leadership style is a person's ability to lead and encourage their subordinates to do everything they are given thoroughly and of course optimally. An authoritarian leadership style is one of the leadership styles used by leaders towards their employees. Authoritarian leadership is a form of leadership where all forms of power, decisions, performance and work motivation are in the hands of the leader himself. The leadership style applied at PT Xyz and Excise is a semi-military authoritarian leadership style. A person's level of work motivation determines how that person performs.